2010
DOI: 10.1177/230949901001800102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Function on Early Postoperative Outcome after Total Hip Arthroplasty

Abstract: Poor preoperative function may affect recovery unfavourably and lead to prolonged pain. Earlier THA in the course of functional decline may associate with better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…For this reason, we have seen much larger improvements in the pelvic specific scoring questionnaires as compared to the general SF-36 forms. Patients with sacroiliac joint disease present with considerable pain and morbidity, with preoperative SF-36 scores falling way below that for both knee and hip arthritis in patients requiring arthroplasty surgery [13,14]. Pain scores reported are also considerably worse than in patients with knee and hip arthritis [14].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have seen much larger improvements in the pelvic specific scoring questionnaires as compared to the general SF-36 forms. Patients with sacroiliac joint disease present with considerable pain and morbidity, with preoperative SF-36 scores falling way below that for both knee and hip arthritis in patients requiring arthroplasty surgery [13,14]. Pain scores reported are also considerably worse than in patients with knee and hip arthritis [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible patients in whom hip preservation failed either chose or were instructed not to participate in such activities to protect their arthroplasties. Johansson et al [12] reported that a lower preoperative HHS correlates with greater postoperative pain and poorer postoperative function. We found lower preoperative HHS did not predict either conversion to THA or poorer postoperative function.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,29 Recent outcome studies have shown that post-operative range of hip motion correlates strongly with functional outcome. 35,36 The purpose of this study was to systematically evaluate the sagittal kinematic and kinetic gait patterns in patients in this early post-operative period, to describe them and to better understand the deficiencies in that gait pattern that may help to develop targeted rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%